Challenges to Physicians: Hospital Immunity and Sham Peer Review - Robert, Poston; Farid, Gharagozloo; Rainer, W.G. Gruessner (Journal of Human Psychology, 2023)
An opinion essay examines hospital immunity doctrines and alleged sham peer review, outlining legal context, patient‑safety implications, and avenues for due process.